2018
DOI: 10.21037/sci.2018.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Ophthalmology Treatment Study: bone marrow derived stem cells in the treatment of Retinitis Pigmentosa

Abstract: The BMSC protocols of the SCOTS achieved meaningful visual acuity improvements or stability in RP that were of statistical significance. Duration of disease did not appear to affect the ability of eyes to respond. Safety was confirmed. Possible mechanisms by which improvement occurred may include transdifferentiation of BMSC into Neuronal Nuclei (NeuN) positive cells, BMSC paracrine secretions or neurotrophic factors and hormones, transfer of mitochondria, release of messenger RNA or other compounds via exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
3
29
0
2
Order By: Relevance
“…Of eyes treated, 45.5% showed improvement averaging a 40.9% increase on the LogMAR vision scale with 45.5% remaining secure during the period of follow up. This is the first time any treatment has proven beneficial to acuity or stabilized vision in a hereditary retinopathy [21].…”
Section: Discussionmentioning
confidence: 81%
“…Of eyes treated, 45.5% showed improvement averaging a 40.9% increase on the LogMAR vision scale with 45.5% remaining secure during the period of follow up. This is the first time any treatment has proven beneficial to acuity or stabilized vision in a hereditary retinopathy [21].…”
Section: Discussionmentioning
confidence: 81%
“…Mesenchymal stem cells (MSCs), a multipotent stromal cell, are currently being tested in clinical trials due to having demonstrated efficacy in a multitude of retinal disease models (reviewed in Ref. 3) 47. Their mechanism of action was shown to be paracrine mediated through the secretion of neurotrophic factors such as nerve growth factor, brain-derived neurotrophic factor,8 and platelet-derived growth factor,9 and more recently, exosomes 10,11…”
mentioning
confidence: 99%
“…Those results have been determined to be statistically significant [17]. Additional reports on other hereditary conditions including Retinitis Pigmentosa [18], Ushers Syndrome [19], and Autosomal Dominant Optic Atrophy [20] have also shown statistically significant visual acuity improvements.…”
Section: Discussionmentioning
confidence: 99%